(untitled) (Journal of Applied and Natural Science, 2015)
The present investigation was done to evaluate the effect of different concentrations of five eco-friendly chemicals in vitro and in vivo, on the management of alternaria blight and yield attributes in Indian mustard (Brassica juncea cv. Varuna). Out of five eco-friendly chemicals, K2SO4 1000 ppm (64.28%) followed by ZnSO4 1000 ppm (63.88%) showed maximum inhibition of mycelial growth in comparison to check. 0.5% concentration of KCl (57.06%) followed by CaSO4 (59.50%) and K2SO4 (62.20%) showed significantly maximum effect on spore germination in comparison to check (74.60%). Spore intensity significantly increased by all the treatments except CaSO4 at 0.5% (40.18%) followed by K2SO4 at 0.5% (29.86%) and ZnSO4 0.75% (5.11% reduction) in comparison to check. The significantly minimum disease index on leaf over check was found by foliar spray of CaSO4 at 0.5%(23.58%) followed by CaSO4 at 1.5% (24.00%) and Na2B4O7.10H2O at 1.5% (24.08%). Na2B4O7.10H2O at 0.75% showed significantly lowest disease index (23.91%) on pod followed by K2SO4 at 1.5% (25.75%) and KCl at 1.5% (26.00%) in comparison to check. CaSO4 at 1.0% showed maximum number of primary branches (7.00), number of secondary branches (13.00) and total yield/ha (1917.30 kg/ha) in comparison to check. The results obtained from the present study suggested that K2SO4 showed maximum in vitro effect on Alternaria brassicae and CaSO4 and Na2B4O7.10H2O are providing maximum reduction of disease and increase in seed yield/ha that leads to efficient alternaria blight disease management strategies in field condition. These eco-friendly chemicals can protect the crops from alternaria blight diseases and increase the production and productivity of the Indian mustard crop.